The role of the northward-directed (sub)surface limb of the Atlantic Meridional Overturning Circulation during the 8.2 ka event - Tegzes, Andrea Diana; Jansen, Eystein; Telford, Richard (Climate of the Past, 2015)
The so-called "8.2 ka event" is widely regarded as a major Holocene climate perturbation. It is most readily identifiable in the oxygen-isotope records from Greenland ice cores as an approximately 160-year-long cold interval between 8250 and 8090 years BP. The prevailing view has been that the cooling over Greenland, and potentially over the northern North Atlantic at least, was triggered by the catastrophic final drainage of the Agassiz–Ojibway proglacial lake as part of the remnant Laurentide Ice Sheet collapsed over Hudson Bay at around 8420 ± 80 years BP. The consequent freshening of surface waters in the northern North Atlantic Ocean and the Nordic Seas resulted in weaker overturning, and hence reduced northward ocean heat transport. We have reconstructed variations in the strength of the eastern branch of the Atlantic Inflow into the Nordic Seas around the time of the lake outbursts. While the initial freshwater forcing may have been even larger than originally thought, as the lake outbursts may have been accompanied by a major iceberg discharge from Hudson Bay, our proxy records from the mid-Norwegian Margin do not evidence a uniquely large slowdown in the eastern branch of the Atlantic Inflow at the time. Therefore, its main role in the 8.2 ka event may have been the (rapid) advection of fresh and cold waters to high northern latitudes, initiating rapid sea-ice expansion and an increase in surface albedo. publishedVersion